Asymmetric conditions of semiconductor converters in the system of electric energy supply to civil aviation enterprises - Пьяных, Б. Е. (Proceedings of National Aviation University (archive), 2000)
The influence of asymmetric conditions on the quality of electric energy of semiconductor converters is considered. The appearance of additional pulsation in the straightened voltage in converter with direct current cell and low frequency modulation in direct converters of frequency is shown